2018
DOI: 10.1016/j.jaccpubpol.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Charity performance reporting, regulatory approaches and standard-setting

Abstract: Internationally, there are strong calls for charities' formal annual reporting to include nonfinancial performance information. Without the international standards common in other sectors, national accounting standard-setters often regulate charities' reporting. Lacking evidence on approaches to encouraging/ mandating charity performance reporting, and the effectiveness of these approaches, we ask: "How have different jurisdictions responded to calls for increasing performance reporting?"We conduct a benchmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 48 publications
1
44
1
1
Order By: Relevance
“…Annual report is an important accountability tool for nonprofit organizations to voluntarily communicate their yearly performance as well as organizational visions, values, and goals with donors, community partners, and public stakeholders both online and offline (Ebrahim, 2003;Mcconville & Cordery, 2018;Saxton, Neely, & Guo, 2014). Since most annual reports are available on foundations' websites, they serve as relatively accessible and transparent sources for documenting an organization's commitment to community leadership.…”
Section: Data Collection Of Annual Reportsmentioning
confidence: 99%
“…Annual report is an important accountability tool for nonprofit organizations to voluntarily communicate their yearly performance as well as organizational visions, values, and goals with donors, community partners, and public stakeholders both online and offline (Ebrahim, 2003;Mcconville & Cordery, 2018;Saxton, Neely, & Guo, 2014). Since most annual reports are available on foundations' websites, they serve as relatively accessible and transparent sources for documenting an organization's commitment to community leadership.…”
Section: Data Collection Of Annual Reportsmentioning
confidence: 99%
“…To assess the potential impact of SEs in addressing inequality in Thailand, we presented financial impacts (from SET investors) and our direct rural SE case studies show how beneficiaries report the impact. We note the difficulties associated with reporting impact (Cordery and Sinclair, 2013, McConville and Cordery, 2018, Nicholls, 2009 and the concerns raised in the public hearings of the Thai SE Act 2019 for SEs to submit only limited amounts of mandatory information, some additional voluntary information, or to provide interview data as evidence of impact. The lack of consensus on reporting means that policy makers should expedite regulations so that SEs can respond appropriately, especially if this causes SEs to de-list.…”
Section: [Insert Figure II Here]mentioning
confidence: 96%
“…However, in defense to their own arguments, Cordery and McConville (2018) suggested that an autocratic approach may lead to several disadvantages. Firstly, a hierarchical system may lead to rule inflexibility, whereby the institution cannot adapt fast enough to changing conditions.…”
Section: Poor Regulatory Designmentioning
confidence: 99%
“…Consequently, Cordery and McConville (2018) recommend that charity governance should consist of a combination of centralized and voluntary institutions, which will dynamically evolve over time. This would enable charity stakeholders to decide amongst themselves how donations should be effectively distributed, but with some level of independent, third-party oversight (Cordery and McConville, 2018). Given that the DLT allows for varying degrees of (de)centralization, it will be interesting to observe its capacities to govern charities over the coming decades.…”
Section: Poor Regulatory Designmentioning
confidence: 99%